Language and Gender: A Case Study of Poetry Fragments By Nizar Qabbani - Wulandari, Wulandari; Nuraisyah, Andini; Fahmi, Muhammad Ilham (Universitas Al Azhar Indonesia, 2024)
Language and gender are two interrelated aspects in linguistic and literary studies. This study aims to analyze the relationship between language and gender in modern Arabic literature, specifically through Nizar Qabbani's verse pieces. Using a Descriptive Qualitative Approach, this study explores how Arabic language represents gender and how cultural norms influence the use of language in literature. The results show that the Arabic language has a gender bias that is reflected in the use of metaphors and sentence structures in Qabbani's verses. The study reveals that Qabbani often uses language to reflect traditional gender views, but also to champion women's rights. This analysis provides insight into the complex relationship between language, culture and gender representation in the context of Arabic literature. From this research, it was found that Nizar Qobbani represented gender with positive things and that he strongly supported the enforcement of gender equality.Keywords – Gender, Language, Nizar Qabbani.